Method for preparing NaP molecular sieve / activated carbon composite material from coal gangue
By preparing NaP molecular sieve/activated carbon composite materials, the problems of insufficient alkali resistance and wear resistance of existing coal gangue-based molecular sieves are solved, and the alkali resistance, wear resistance and hydrophilicity of composite materials are improved, and suitable for saline-alkali earth fertilizers Additives to promote plant growth.
Patent Information
- Application Number
- CN202411626543.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The alkali resistance and wear resistance of existing coal gangue-based molecular sieve need to be further improved.
By preparing NaP molecular sieve/activated carbon composite materials, including activated coal gangue, hydrothermal crystallization, vapor deposition to form a carbon layer, thermal isostatic treatment and oxidation treatment, the compact carbon coating and active groups are formed, and the material is enhanced Alkaline resistance and wear resistance, and enhance its hydrophilicity by cross-linking of hydrophilic modifiers.
The alkali resistance, wear resistance and hydrophilicity of the composite molecular sieve is significantly improved, making it suitable for additives for saline-alkali earth fertilizers, and improving the growth rate and survival rate of plants.
Smart Images

Figure CN119461412A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coal-based solid waste resource utilization, and in particular to a method for preparing a NaP molecular sieve / activated carbon composite material by using coal gangue. Background Art
[0002] As a low-cost industrial waste, coal gangue has been widely used in the preparation of molecular sieves in recent years. The molecular sieves prepared by the hydrothermal method of coal gangue have good performance in wear resistance and alkali resistance. By adjusting the physical and chemical properties of coal gangue, the mechanical strength of the molecular sieve can be effectively improved, so that it can still maintain good stability in high load and friction environment. Its high silicon-aluminum ratio helps the molecular sieve to maintain a good framework structure under alkaline conditions and avoid deconstruction or performance degradation in a strong alkaline environment. This comprehensive improvement in performance makes coal gangue molecular sieves show broad prospects in environmental protection, resource recycling and industrial applications.
[0003] Prior art CN114988426A discloses a gangue-based molecular sieve and an alkali fusion-hydrothermal preparation method thereof, wherein gangue powder and sodium hydroxide are mixed and ground and then roasted to obtain alkali fused gangue, and the alkali fused gangue, sodium aluminate and water are mixed and stirred uniformly, and then subjected to hydrothermal reaction to obtain a molecular sieve crude product, and the molecular sieve crude product is filtered, washed and dried in sequence to obtain a gangue-based molecular sieve;
[0004] The alkali melting-hydrothermal preparation method of the gangue-based molecular sieve of the invention uses gangue powder, sodium hydroxide and sodium aluminate as raw materials, combines alkali melting method and hydrothermal method to prepare the gangue-based molecular sieve with excellent structural properties, simplifies the preparation process of the molecular sieve, and improves the synthesis efficiency of the molecular sieve.
[0005] However, the above patent uses a pre-treatment step of mixing and grinding coal gangue powder and sodium hydroxide and then roasting. However, the carbon structure in the coal gangue is removed after roasting, which reduces the utilization rate of the raw materials. In addition, the molecular sieve obtained by hydrothermal crystallization lacks the support and protection of the carbon structure, and its wear resistance needs to be further improved. In addition, the molecular structure after crystallization is a single metal oxide structure, which further leads to poor alkali resistance of the molecular sieve and reduces the application range of the material.
[0006] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention
[0007] The purpose of the present invention is to provide a method for preparing NaP molecular sieve / activated carbon composite material using coal gangue, which is used to solve the technical problem in the prior art that the alkali resistance and wear resistance of coal gangue-based molecular sieves need to be further improved.
[0008] The object of the present invention can be achieved by the following technical scheme: A method for preparing NaP molecular sieve / activated carbon composite material using coal gangue, comprising the following steps:
[0009] S1. Place the pre-treated coal gangue and activation liquid in a reactor, raise the temperature of the reactor to 40-50°C, keep warm and activate for 2-3 days, and post-treat to obtain activated coal gangue;
[0010] S2, putting the activated coal gangue and the oxidizing liquid into a special reactor, and after the reactor is sealed, the temperature is raised to 100-180°C, and the temperature is kept for 6-36 hours, and the crystallized molecular sieve is obtained by post-processing;
[0011] The reaction equation for preparing crystallized molecular sieve is: 10Na 2 SiO 3 +6NaAlO 2 +22H 2 O→Na 6 Al 6 Si 10 O 32 12H 2 O+20NaOH
[0012] The reaction principle of preparing crystallized molecular sieves: Under hydrothermal conditions, the silicon and aluminum ions in the reactants interact with each other under high temperature and high pressure. Through dissolution, ion exchange and recrystallization, sodium silicate (Na 2 SiO 3 ) provides silicon source, sodium aluminate (NaAlO 2 ) provides an aluminum source, and water and sodium hydroxide (NaOH) work together to promote silicon and aluminum to form a crystal with a regular pore structure, and finally a molecular sieve is prepared.
[0013] S3, adding the crystallized molecular sieve into a vapor deposition device, obtaining a carbonized molecular sieve through vapor deposition, and obtaining a carbon-coated molecular sieve through hot isostatic pressing;
[0014] S4, adding the oxidized molecular sieve, the hydrophilic modifier, the catalyst and tetrahydrofuran into the reaction kettle, raising the temperature of the reaction kettle to 40-50°C, keeping the temperature for reaction for 2-4h, and post-treating to obtain the composite molecular sieve.
[0015] The reaction principle for preparing the composite molecular sieve is as follows: under the catalysis of the catalyst, the isocyanate group of the hydrophilic modifier reacts with the hydroxyl group on the carbon-coated molecular sieve, and finally the composite molecular sieve is prepared.
[0016] Furthermore, in step S1, the pretreatment step is: after rinsing the gangue with ethanol and deionized water for 3-5 times, the gangue is transferred to a drying oven at a temperature of 80°C for vacuum drying until the gangue is constant weight, and crushed with a crusher, and then ground in a grinder, sieved with a 100-mesh screen to obtain pretreated gangue; the dosage ratio of the pretreated gangue and the activation solution is 2-3g:20-30mL, and the activation solution is prepared by configuring 2-3mol / L sodium hydroxide solution and sodium dodecyl sulfate in a dosage ratio of 20-30mL:1-2g, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction liquid is filtered to collect the filter cake, the filter cake is rinsed with ethanol and deionized water for 3-5 times, and the filter cake is transferred to a drying oven at a temperature of 80°C for vacuum drying until the filter cake is constant weight to obtain activated gangue.
[0017] Furthermore, in step S2, the dosage ratio of activated coal gangue and oxidizing liquid is 2-3g:20-30mL, the oxidizing liquid is prepared by hydrogen peroxide, ferrous chloride, hydrochloric acid and deionized water in a dosage ratio of 2-3g:4-6g:3-5g:20-30mL, the material of the special reactor is stainless steel lined with polytetrafluoroethylene, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction liquid is transferred to an ultrasonic instrument for ultrasonication, the ultrasonic frequency is 20-40kHz, after ultrasonication for 20-40min, the reaction liquid is filtered to collect the filter cake, the filter cake is rinsed with ethanol and deionized water for 3-5 times, and then the filter cake is transferred to a drying oven at a temperature of 80°C for vacuum drying until the filter cake has a constant weight to obtain a crystallized molecular sieve.
[0018] Furthermore, in step S3, the vapor deposition operation is as follows: after nitrogen is introduced to exhaust the air in the reaction chamber, the temperature of the reaction chamber is raised to 800-1200°C, the gas pressure is set to 1000-1200Pa, and a mixed gas of methane and nitrogen in a volume ratio of 1-2:20 is introduced, the gas flow rate is 600-800sccm, and the heat treatment is carried out for 2-4h to obtain a carbon-coated molecular sieve.
[0019] Furthermore, in step S3, the hot isostatic pressing operation is as follows: adding the carbonized molecular sieve into a hot isostatic pressing furnace, raising the temperature of the hot isostatic pressing device to 1500-1800°C, and the pressure to 200-300MPa, and after high temperature and high pressure treatment for 4-6h, a carbon-coated molecular sieve is obtained.
[0020] Furthermore, in step S4, the amount ratio of the oxidized molecular sieve, the hydrophilic modifier, the catalyst and tetrahydrofuran is 8-10g:3-5g:0.6-1.0g:50-60mL, and the catalyst is a mixture of dibutyltin dichloride and hydroquinone in an amount ratio of 0.3-0.5g:0.3-0.5g. The post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction liquid is filtered to collect the filter cake, and the filter cake is rinsed with ethanol and deionized water for 3-5 times, and then the filter cake is transferred to a drying oven at a temperature of 80°C for vacuum drying until the filter cake has a constant weight to obtain a composite molecular sieve.
[0021] Furthermore, in step S4, the preparation method of the oxidized molecular sieve is as follows: add the carbon-coated molecular sieve and 98.0wt% sulfuric acid to a reactor at a temperature of 0-5°C and stir, keep warm and stir for 10-15 minutes, add sodium chlorate to the reactor, keep the temperature of the reactor at 0-5°C and react for 2-4 hours, use a saturated sodium hydroxide solution to adjust the pH of the reaction system to 7, and post-treat to obtain the oxidized molecular sieve.
[0022] The reaction principle of preparing oxidized molecular sieves is: sulfuric acid provides an acidic environment, making the structure of the carbon-coated molecular sieve more active, creating conditions for the oxidation reaction. Sodium chlorate will decompose to produce chloric acid and oxygen under acidic conditions. The strong oxidizing effect of chloric acid can oxidize the carbon layer of the carbon-coated molecular sieve to produce a carbon-coated molecular sieve containing various oxygen functional groups, such as epoxy groups, carboxyl groups, hydroxyl groups, etc.
[0023] Furthermore, the usage ratio of carbon-coated molecular sieve, 98.0wt% sulfuric acid and sodium chlorate is 5-8g:30-40g:3-5g, the stirring rate of the reactor is 80-120rpm, and the post-treatment includes: after the temperature of the reactor is raised to room temperature, the reaction liquid is filtered to collect the filter cake, the filter cake is washed 3-5 times with deionized water, and the filter cake is placed in a drying oven at a temperature of 80°C and vacuum dried until the filter cake has a constant weight to obtain an oxidized molecular sieve.
[0024] Furthermore, in step S4, the preparation method of the hydrophilic modifier comprises the following steps:
[0025] A1, add trifluoroethyl methacrylate, 1-allyloxy-2,3-propylene oxide, 3-(methacryloyloxy)propyltrimethoxysilane, isocyanatoethyl methacrylate and toluene into a reaction kettle and introduce nitrogen protection, stir at room temperature for 10-15 minutes to obtain a reaction liquid precursor solution;
[0026] A2. Add the reaction liquid precursor and azobisisobutyronitrile into the reactor and stir. Raise the temperature of the reactor to 70-80° C. and keep the temperature for 2-4 hours. Post-treat to obtain a hydrophilic modifier.
[0027] The reaction equation for preparing the hydrophilic modifier is:
[0028]
[0029] Where:
[0030] The reaction principle for preparing the hydrophilic modifier is as follows: under heating and the catalysis of a free radical initiator, trifluoroethyl methacrylate, 1-allyloxy-2,3-propylene oxide, 3-(methacryloyloxy)propyltrimethoxysilane and isocyanoethyl methacrylate undergo free radical polymerization to finally prepare the hydrophilic modifier.
[0031] Furthermore, in step A1, the amount ratio of trifluoroethyl methacrylate, 1-allyloxy-2,3-propylene oxide, 3-(methacryloyloxy)propyltrimethoxysilane, isocyanoethyl methacrylate and toluene is 5-8g:4-5g:10-12g:8-10g:80-100mL, and the stirring rate of the reactor is 80-120rpm; in step A2, the amount ratio of the reaction liquid precursor and azobisisobutyronitrile is 50-60mL:2-3g, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction liquid is placed in a rotary evaporator with a water bath temperature of 80-100°C, and the reduced pressure distillation is performed until no liquid is extracted to obtain a hydrophilic modifier.
[0032] The present invention has the following beneficial effects:
[0033] 1. The present invention activates the surface structure of coal gangue by preparing an activation liquid, so that it has a richer pore structure and enhances its adsorption capacity, and uses a hydrothermal method to crystallize and pre-oxidize the coal gangue to retain the carbon structure in the coal gangue, and generate some active groups to promote carbon deposition on the surface of the crystallized molecular sieve to deposit a carbon layer, and through hot isostatic pressing treatment, the carbon layer undergoes molecular rearrangement to form a tight carbon coating on the molecular sieve, thereby improving the alkali resistance and wear resistance of the material, and forms active groups on the surface of the molecular sieve after oxidation treatment, and cross-links with the prepared hydrophilic modifier to make the surface and pores of the composite molecular sieve more hydrophilic, promote water retention, thereby improving its performance as a saline-alkali soil fertilizer, and finally obtain a wear-resistant, alkali-resistant and hydrophilic composite molecular sieve, which can be used as an additive for saline-alkali soil fertilizer.
[0034] 2. In the process of modifying the crystallized molecular sieve, the present invention uses a vapor deposition method to form a tightly structured carbon layer on its surface, and obtains a more stable carbon layer structure after atomic rearrangement after hot isostatic pressing, which significantly enhances the wear resistance and corrosion resistance of the material. The carbon layer on the surface of the molecular sieve is further oxidized to introduce a large number of active functional groups such as hydroxyl, epoxy and carboxyl groups on its surface, laying the foundation for its further modification.
[0035] 3. In the process of hydrophilic modification of the oxidized molecular sieve, the present invention prepares hydrophilic and alkali-resistant polymer segments by selecting reactive monomers for free radical polymerization. The polymer segments have a large number of hydrophilic functional groups such as ester groups and ether groups, which cooperate with a large number of pores of the molecular sieve to enhance the water retention capacity and biological affinity of the molecular sieve. When used as a fertilizer additive for saline-alkali soil, its high specific surface area and porosity have a good adsorption effect on biomass fertilizer, which can achieve the effect of reducing application and increasing efficiency, and provide water to plants by gradually releasing carbon, improve the soil quality of saline-alkali soil, enhance the microenvironment of the land, and greatly improve the survival rate and growth rate of plants. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0037] Figure 1 This is a SEM photo of the composite molecular sieve prepared in Example 3;
[0038] Figure 2 This is an image of a compound fertilizer configured with the composite molecular sieve prepared in Example 3 in a performance test;
[0039] Figure 3 XRD spectra of crystallized molecular sieves at different crystallization temperatures;
[0040] Figure 4 XRD spectra of crystallized molecular sieves at different crystallization times;
[0041] Figure 5 This is a SEM photo of the crystallized molecular sieve crystallized at 160°C for 12 hours;
[0042] Figure 6 This is a SEM photo of the crystallized molecular sieve crystallized at 160°C for 36 hours;
[0043] Figure 7 This is the distribution diagram of O, Na, Si and Al elements in the composite molecular sieve prepared in Example 3;
[0044] Figure 8 This is a distribution diagram of C, Ti, Mg, Ca, K, Fe, S and F elements in the composite molecular sieve prepared in Example 3;
[0045] Fig. 9 This is the EDS spectrum of the atomic content of the composite molecular sieve prepared in Example 3;
[0046] Fig.10 These are images of the growth of plants in a saline-alkali soil potted experiment. DETAILED DESCRIPTION
[0047] The technical scheme of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0048] Example 1
[0049] This embodiment provides a method for preparing a NaP molecular sieve / activated carbon composite material using coal gangue, comprising the following steps:
[0050] S1. Preparation of crystallized molecular sieve
[0051] After washing the gangue with ethanol and deionized water for 3 times, the gangue was transferred to a drying oven at a temperature of 80°C for vacuum drying until the gangue had a constant weight, crushed with a crusher, and then ground in a grinder, and sieved with a 100-mesh screen to obtain pre-treated gangue;
[0052] Weigh: 24.0 mL of 2 mol / L sodium hydroxide solution and 1.6 g of sodium dodecyl sulfate according to the usage ratio to obtain an activation solution;
[0053] Weigh: 5.4 g of pre-treated coal gangue and 48.0 mL of activation solution are placed in a reactor, the reactor temperature is raised to 40°C, and the activation is maintained for 2 days. After the reaction is completed, the reactor temperature is lowered to room temperature, the reaction liquid is filtered to collect the filter cake, and the filter cake is rinsed with ethanol and deionized water for 3 times, and then the filter cake is transferred to a drying oven at a temperature of 80°C for vacuum drying until the filter cake has a constant weight, thereby obtaining activated coal gangue;
[0054] Weigh: 5.4 g hydrogen peroxide, 9.6 g ferrous chloride, 8.4 g hydrochloric acid and 54.0 mL deionized water to prepare an oxidation solution;
[0055] Weigh: 5.4g activated coal gangue and 48.0mL oxidizing liquid are put into a stainless steel reactor lined with polytetrafluoroethylene. After the reactor is sealed, the temperature is raised to 100°C and the reaction is kept warm for 6 hours. After the reaction is completed, the temperature of the reactor is lowered to room temperature, and the reaction liquid is transferred to an ultrasonic instrument for ultrasonication at a frequency of 20kHz. After ultrasonication for 20 minutes, the reaction liquid is filtered to collect the filter cake. After rinsing the filter cake with ethanol and deionized water for 3 times, the filter cake is transferred to a drying oven at a temperature of 80°C for vacuum drying until the filter cake has a constant weight to obtain a crystallized molecular sieve.
[0056] S2. Preparation of Oxidized Molecular Sieve
[0057] The crystallized molecular sieve was added into a vapor deposition device, and after nitrogen was introduced to exhaust the air in the reaction chamber, the temperature of the reaction chamber was raised to 800°C, the gas pressure was set to 1000Pa, and a mixed gas of methane and nitrogen in a volume ratio of 1:20 was introduced, the gas flow rate was 600sccm, and the heat treatment was carried out for 2h to obtain a carbon-coated molecular sieve;
[0058] The carbonized molecular sieve is added into a hot isostatic pressing furnace, the temperature of the hot isostatic pressing device is increased to 1500°C, the pressure is increased to 200MPa, and after high temperature and high pressure treatment for 4 hours, a carbon-coated molecular sieve is obtained;
[0059] Weigh: 12.4g of carbon-coated molecular sieve and 64.0g of 98.0wt% sulfuric acid are added to a reactor at a temperature of 5°C and stirred at a stirring rate of 80rpm. After keeping warm and stirring for 10min, 8.4g of sodium chlorate is added to the reactor. The temperature of the reactor is maintained at 5°C and reacted for 2h. A saturated sodium hydroxide solution is used to adjust the pH of the reaction system to 7. After the temperature of the reactor is raised to room temperature, the reaction liquid is filtered to collect the filter cake, and the filter cake is washed 3 times with deionized water. The filter cake is placed in a drying oven at a temperature of 80°C and vacuum dried until the filter cake has a constant weight to obtain an oxidized molecular sieve.
[0060] S3. Preparation of composite molecular sieve
[0061] Weigh: 12.4 g of trifluoroethyl methacrylate, 9.6 g of 1-allyloxy-2,3-propylene oxide, 21.0 g of 3-(methacryloyloxy)propyltrimethoxysilane, 18.0 g of isocyanoethyl methacrylate and 180.0 mL of toluene, add into a reaction kettle and introduce nitrogen protection, stir at room temperature for 10 min at a stirring rate of 80 rpm to obtain a reaction liquid precursor solution;
[0062] Weigh: 100.0 mL of reaction liquid precursor and 5.0 g of azobisisobutyronitrile are added to the reactor and stirred. The temperature of the reactor is raised to 50° C. and the reaction is kept warm for 2 hours. After the reaction is completed, the temperature of the reactor is lowered to room temperature, and the reaction liquid is placed in a rotary evaporator with a water bath temperature of 80° C. and distilled under reduced pressure until no liquid is produced to obtain a hydrophilic modifier;
[0063] Weigh: 18.0g of oxidized molecular sieve, 9.6g of hydrophilic modifier, 0.8g of dibutyltin dichloride, 0.8g of hydroquinone and 100.0mL of tetrahydrofuran are added into the reactor, the temperature of the reactor is raised to 40°C, and the reaction is kept warm for 2h. After the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction liquid is filtered to collect the filter cake, and the filter cake is rinsed with ethanol and deionized water for 3 times, and then the filter cake is transferred to a drying oven at a temperature of 80°C for vacuum drying until the filter cake has a constant weight to obtain a composite molecular sieve.
[0064] Example 2
[0065] This embodiment provides a method for preparing a NaP molecular sieve / activated carbon composite material using coal gangue, comprising the following steps:
[0066] S1. Preparation of crystallized molecular sieve
[0067] After washing the gangue with ethanol and deionized water for 5 times, the gangue was transferred to a drying oven at a temperature of 80°C for vacuum drying until the gangue had a constant weight, crushed with a crusher, and then ground in a grinder, and sieved with a 100-mesh screen to obtain pre-treated gangue;
[0068] Weigh: 30.0 mL of 3 mol / L sodium hydroxide solution and 2.0 g of sodium dodecyl sulfate according to the dosage ratio to obtain an activation solution;
[0069] Weigh: 5.4 g of pre-treated coal gangue and 54.0 mL of activation solution are placed in a reactor, the reactor temperature is raised to 50°C, and the activation is maintained for 3 days. After the reaction is completed, the reactor temperature is lowered to room temperature, the reaction liquid is filtered to collect the filter cake, and the filter cake is rinsed with ethanol and deionized water for 5 minutes, and then the filter cake is transferred to a drying oven at a temperature of 80°C for vacuum drying until the filter cake has a constant weight, thereby obtaining activated coal gangue;
[0070] Weigh: 5.4 g hydrogen peroxide, 9.6 g ferrous chloride, 8.4 g hydrochloric acid and 54.0 mL deionized water to prepare an oxidation solution;
[0071] Weigh: 5.4g activated coal gangue and 60.0mL oxidizing liquid are put into a stainless steel reactor lined with polytetrafluoroethylene. After the reactor is sealed, the temperature is raised to 180°C and the reaction is kept warm for 36 hours. After the reaction is completed, the temperature of the reactor is lowered to room temperature, and the reaction liquid is transferred to an ultrasonic instrument for ultrasonication at a frequency of 40kHz. After ultrasonication for 40 minutes, the reaction liquid is filtered to collect the filter cake. After rinsing the filter cake with ethanol and deionized water for 5 minutes, the filter cake is transferred to a drying oven at a temperature of 80°C for vacuum drying until the filter cake has a constant weight to obtain a crystallized molecular sieve.
[0072] S2. Preparation of Oxidized Molecular Sieve
[0073] The crystallized molecular sieve was added into a vapor deposition device, and after nitrogen was introduced to exhaust the air in the reaction chamber, the temperature of the reaction chamber was raised to 800°C, the gas pressure was set to 1200Pa, and a mixed gas of methane and nitrogen in a volume ratio of 2:20 was introduced, the gas flow rate was 800sccm, and the heat preservation treatment was performed for 4 hours to obtain a carbon-coated molecular sieve;
[0074] The carbonized molecular sieve is added into a hot isostatic pressing furnace, the temperature of the hot isostatic pressing device is increased to 1800°C, the pressure is increased to 300MPa, and after high temperature and high pressure treatment for 6 hours, a carbon-coated molecular sieve is obtained;
[0075] Weigh: 12.4g carbon-coated molecular sieve and 72.0g98.0wt% sulfuric acid are added to a reactor at a temperature of 3°C and stirred at a stirring rate of 120rpm. After keeping warm and stirring for 15 minutes, 3-5g sodium chlorate is added to the reactor. The temperature of the reactor is maintained at 3°C and reacted for 4 hours. A saturated sodium hydroxide solution is used to adjust the pH of the reaction system to 7. After the temperature of the reactor is raised to room temperature, the reaction liquid is filtered to collect the filter cake, and the filter cake is washed 5 times with deionized water. The filter cake is placed in a drying oven at a temperature of 80°C and vacuum dried until the filter cake has a constant weight to obtain an oxidized molecular sieve.
[0076] S3. Preparation of composite molecular sieve
[0077] Weigh: 14.2 g of trifluoroethyl methacrylate, 9.6 g of 1-allyloxy-2,3-propylene oxide, 21.0 g of 3-(methacryloyloxy)propyltrimethoxysilane, 18.4 g of isocyanoethyl methacrylate and 180.0 mL of toluene, add into a reaction kettle and stir, and introduce nitrogen protection, stir at room temperature for 12 min, and the stirring rate is 120 rpm to obtain a reaction liquid precursor solution;
[0078] Weigh: 120.0 mL of reaction liquid precursor and 5.4 g of azobisisobutyronitrile are added to the reactor and stirred. The temperature of the reactor is raised to 60° C. and the reaction is kept warm for 4 hours. After the reaction is completed, the temperature of the reactor is lowered to room temperature, and the reaction liquid is placed in a rotary evaporator with a water bath temperature of 100° C. and distilled under reduced pressure until no liquid is produced to obtain a hydrophilic modifier;
[0079] Weigh: 18.0g of oxidized molecular sieve, 8.4g of hydrophilic modifier, 1.0g of dibutyltin dichloride, 1.0g of hydroquinone and 100.0mL of tetrahydrofuran are added into the reactor, the temperature of the reactor is raised to 50°C, and the reaction is kept warm for 4h. After the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction liquid is filtered to collect the filter cake, and the filter cake is rinsed with ethanol and deionized water for 5, and then the filter cake is transferred to a drying oven at a temperature of 80°C for vacuum drying until the filter cake has a constant weight to obtain a composite molecular sieve.
[0080] Example 3
[0081] This embodiment provides a method for preparing a NaP molecular sieve / activated carbon composite material using coal gangue, comprising the following steps:
[0082] S1. Preparation of crystallized molecular sieve
[0083] After washing the gangue with ethanol and deionized water for 4 times, the gangue was transferred to a drying oven at a temperature of 80°C for vacuum drying until the gangue had a constant weight, crushed with a crusher, and then ground in a grinder, and sieved with a 100-mesh screen to obtain pre-treated gangue;
[0084] Weigh: 25 mL of 2.5 mol / L sodium hydroxide solution and 2.0 g of sodium dodecyl sulfate according to the dosage ratio to obtain an activation solution;
[0085] Weigh: 5.4 g of pre-treated coal gangue and 54.0 mL of activation solution are placed in a reactor, the reactor temperature is raised to 45 ° C, and the activation is kept warm for 3 days. After the reaction is completed, the reactor temperature is lowered to room temperature, the reaction liquid is filtered to collect the filter cake, and the filter cake is rinsed with ethanol and deionized water for 4, and then the filter cake is transferred to a drying oven at a temperature of 80 ° C for vacuum drying until the filter cake has a constant weight, thereby obtaining activated coal gangue;
[0086] Weigh: 5.4 g hydrogen peroxide, 10.0 g ferrous chloride, 9.6 g hydrochloric acid and 50.0 mL deionized water to prepare an oxidation solution;
[0087] Weigh: 5.4g activated coal gangue and 54.0mL oxidizing liquid are put into a stainless steel reactor lined with polytetrafluoroethylene. After the reactor is sealed, the temperature is raised to 150°C and the reaction is kept warm for 18 hours. After the reaction is completed, the temperature of the reactor is lowered to room temperature, and the reaction liquid is transferred to an ultrasonic instrument for ultrasonication at a frequency of 36kHz. After ultrasonication for 30 minutes, the reaction liquid is filtered to collect the filter cake. After rinsing the filter cake with ethanol and deionized water for 4, the filter cake is transferred to a drying oven at a temperature of 80°C for vacuum drying until the filter cake has a constant weight to obtain a crystallized molecular sieve.
[0088] S2. Preparation of Oxidized Molecular Sieve
[0089] The crystallized molecular sieve was added into a vapor deposition device, and after nitrogen was introduced to exhaust the air in the reaction chamber, the temperature of the reaction chamber was raised to 1000°C, the gas pressure was set to 1100 Pa, and a mixed gas of methane and nitrogen in a volume ratio of 2:20 was introduced, the gas flow rate was 700 sccm, and the heat treatment was carried out for 3 hours to obtain a carbon-coated molecular sieve;
[0090] The carbonized molecular sieve is added into a hot isostatic pressing furnace, the temperature of the hot isostatic pressing device is increased to 1650°C, the pressure is increased to 250MPa, and after high temperature and high pressure treatment for 2h, a carbon-coated molecular sieve is obtained;
[0091] Weigh: 12.0g of carbon-coated molecular sieve and 72.0g of 98.0wt% sulfuric acid are added to a reactor at a temperature of 0°C and stirred at a stirring rate of 100rpm. After keeping warm and stirring for 12 minutes, 4.0g of sodium chlorate is added to the reactor. The temperature of the reactor is maintained at 0°C for reaction for 3 hours. A saturated sodium hydroxide solution is used to adjust the pH of the reaction system to 7. After the temperature of the reactor is raised to room temperature, the reaction liquid is filtered to collect the filter cake, and the filter cake is washed 4 times with deionized water. The filter cake is placed in a drying oven at a temperature of 80°C and vacuum dried until the filter cake has a constant weight to obtain an oxidized molecular sieve.
[0092] S3. Preparation of composite molecular sieve
[0093] Weigh: 12.0 g of trifluoroethyl methacrylate, 8.0 g of 1-allyloxy-2,3-propylene oxide, 20.0 g of 3-(methacryloyloxy)propyltrimethoxysilane, 20.0 g of isocyanoethyl methacrylate and 180.0 mL of toluene, add into a reaction kettle, stir and introduce nitrogen protection, stir at room temperature for 15 min, and the stirring rate is 100 rpm to obtain a reaction liquid precursor solution;
[0094] Weigh: 100.0 mL of reaction liquid precursor and 5.4 g of azobisisobutyronitrile are added to the reactor and stirred. The temperature of the reactor is raised to 55° C. and the reaction is kept warm for 3 hours. After the reaction is completed, the temperature of the reactor is lowered to room temperature, and the reaction liquid is placed in a rotary evaporator with a water bath temperature of 90° C. and distilled under reduced pressure until no liquid is produced to obtain a hydrophilic modifier;
[0095] Weigh: 18.0g of oxidized molecular sieve, 9.6g of hydrophilic modifier, 0.8g of dibutyltin dichloride, 0.8g of hydroquinone and 100.0mL of tetrahydrofuran are added into the reactor, the temperature of the reactor is raised to 45°C, and the reaction is kept warm for 3h. After the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction liquid is filtered to collect the filter cake, and the filter cake is rinsed with ethanol and deionized water for 4, and then the filter cake is transferred to a drying oven at a temperature of 80°C for vacuum drying until the filter cake has a constant weight to obtain a composite molecular sieve.
[0096] Comparative Example 1
[0097] The difference between this comparative example and Example 3 is that in step S1, the activation solution is not used.
[0098] Comparative Example 2
[0099] The difference between this comparative example and Example 3 is that in step S2, the step of preparing the oxidized molecular sieve is eliminated, and in step S3, the oxidized molecular sieve is replaced by an equal amount of carbon-coated molecular sieve.
[0100] Comparative Example 3
[0101] The difference between this comparative example and Example 3 is that in step S3, the step of preparing a hydrophilic modifier is omitted, and in step S3, an equal amount of polyvinyl alcohol replaces the hydrophilic modifier.
[0102] Performance Testing:
[0103] The wear rate and static formaldehyde adsorption rate of the composite molecular sieves prepared in Examples 1-3 and Comparative Examples 1-3 were measured with reference to the standard HG / T 2524-2010 "Method for determination of static water adsorption of molecular sieves";
[0104] Referring to the standard GB / T 6287-2021 "Determination method for static water adsorption of molecular sieves", the static water adsorption amount of the composite molecular sieves prepared in Examples 1-3 and Comparative Examples 1-3 was measured;
[0105] Referring to the standard GB / T 8770-2014 "Determination method of dynamic water adsorption of molecular sieves", the dynamic water adsorption of the composite molecular sieves prepared in Examples 1-3 and Comparative Examples 1-3 was measured;
[0106] The composite molecular sieves prepared in Examples 1-3 and Comparative Examples 1-3 were immersed in a sodium hydroxide solution with a pH of 9 for 36 days, and the mass loss rate of the composite molecular sieves was measured. The specific data are shown in Table 1;
[0107] Take 4 portions of 500mL of dry saline-alkali soil and place them in flower pots, numbered 1#, 2#, 3#, and 4#. Among them, 1# is pure saline-alkali soil, 2# is saline-alkali soil with the same volume of crushed coal gangue added, 3# is saline-alkali soil with the same volume of coal gangue powder added, and 4# is saline-alkali soil with the same volume of composite molecular sieve prepared in Example 3 and dry sheep manure mixed at a mass ratio of 1:10g to obtain a composite fertilizer. Plants were planted in an open-air environment, watered with the same volume every day, observed continuously for one month, and the growth of plants in different soil environments was recorded. The specific data are shown in Table 2.
[0108] Table 1-Performance test data of each sample
[0109]
[0110] Table 2-Plant growth status of each sample
[0111]
[0112] Data Analysis:
[0113] Comparative analysis of the data in Table 1 above shows that the wear rate of the composite molecular sieve prepared by the present invention is 0.8%, the static formaldehyde adsorption rate is 29.6%, the static water adsorption capacity is 38.5%, the dynamic water adsorption capacity is 35.1%, and the mass loss rate of alkali liquid is 0.2%. At the same time, after the composite fertilizer obtained by mixing the prepared composite molecular sieve and dry sheep manure is added to saline-alkali soil, the new seedlings of the plants are strong, and a microbial environment appears on the surface of the saline-alkali soil;
[0114] Data description:
[0115] The present invention activates the surface structure of coal gangue by preparing an activation liquid so that the surface structure of the coal gangue has a richer pore structure and its adsorption capacity is enhanced; the coal gangue is crystallized and pre-oxidized by a hydrothermal method to retain the carbon structure in the coal gangue, and some active groups are generated to promote carbon deposition on the surface of the crystallized molecular sieve to deposit a carbon layer; the carbon layer is subjected to a hot isostatic pressing treatment to cause molecular rearrangement so as to form a tight carbon coating on the molecular sieve, thereby improving the alkali resistance and wear resistance of the material; active groups are formed on the surface of the molecular sieve after oxidation treatment; the surface and pores of the composite molecular sieve are made more hydrophilic by cross-linking with a prepared hydrophilic modifier, thereby promoting the retention of water, thereby improving the performance of the composite molecular sieve as a saline-alkali soil fertilizer, and finally obtaining a wear-resistant, alkali-resistant and hydrophilic composite molecular sieve additive for saline-alkali soil fertilizer.
[0116] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A method for preparing NaP molecular sieve / activated carbon composite material from coal gangue, characterized in that: The following steps are involved: S1. Place the pre-treated coal gangue and activation liquid in a reactor, raise the temperature of the reactor to 40-50°C, keep warm and activate for 2-3 days, and post-treat to obtain activated coal gangue; S2, putting the activated coal gangue and the oxidizing liquid into a special reactor, and after the reactor is sealed, the temperature is raised to 100-180°C, and the temperature is kept for 6-36 hours, and the crystallized molecular sieve is obtained by post-processing; S3, adding the crystallized molecular sieve into a vapor deposition device, obtaining a carbonized molecular sieve through vapor deposition, and obtaining a carbon-coated molecular sieve through hot isostatic pressing; S4, adding the oxidized molecular sieve, the hydrophilic modifier, the catalyst and tetrahydrofuran into the reaction kettle, raising the temperature of the reaction kettle to 40-50°C, keeping the temperature for reaction for 2-4h, and post-treating to obtain the composite molecular sieve.
2. The method for preparing NaP molecular sieve / activated carbon composite material from coal gangue according to claim 1, characterized in that: In step S1, the pretreatment step is: after washing the gangue with ethanol and deionized water for 3-5 times, the gangue is transferred to a drying oven at a temperature of 80°C for vacuum drying until the gangue has a constant weight, and crushed with a crusher, and then ground in a grinder, and sieved with a 100-mesh sieve to obtain pretreated gangue; the dosage ratio of the pretreated gangue and the activation solution is 2-3g:20-30mL, and the activation solution is prepared by configuring 2-3mol / L sodium hydroxide solution and sodium dodecyl sulfate in a dosage ratio of 20-30mL:1-2g.
3. The method for preparing NaP molecular sieve / activated carbon composite material from coal gangue according to claim 1, characterized in that: In step S2, the dosage ratio of activated coal gangue and oxidizing liquid is 2-3g:20-30mL, the oxidizing liquid is prepared by hydrogen peroxide, ferrous chloride, hydrochloric acid and deionized water in a dosage ratio of 2-3g:4-6g:3-5g:20-30mL, and the material of the special reactor is stainless steel lined with polytetrafluoroethylene.
4. The method for preparing NaP molecular sieve / activated carbon composite material from coal gangue according to claim 1, characterized in that: In step S3, the vapor deposition operation is as follows: after nitrogen is introduced to exhaust the air in the reaction chamber, the temperature of the reaction chamber is raised to 800-1200°C, the gas pressure is set to 1000-1200Pa, and a mixed gas of methane and nitrogen in a volume ratio of 1-2:20 is introduced, the gas flow rate is 600-800sccm, and the heat treatment is carried out for 2-4h to obtain a carbonized molecular sieve.
5. The method for preparing NaP molecular sieve / activated carbon composite material from coal gangue according to claim 1, characterized in that: In step S3, the hot isostatic pressing operation is as follows: adding the carbonized molecular sieve into a hot isostatic pressing furnace, raising the temperature of the hot isostatic pressing device to 1500-1800°C, and the pressure to 200-300MPa, and after high temperature and high pressure treatment for 4-6h, a carbon-coated molecular sieve is obtained.
6. The method for preparing NaP molecular sieve / activated carbon composite material from coal gangue according to claim 1, characterized in that: In step S4, the amount ratio of the oxidized molecular sieve, the hydrophilic modifier, the catalyst and tetrahydrofuran is 8-10g:3-5g:0.6-1.0g:50-60mL, and the catalyst is a mixture of dibutyltin dichloride and hydroquinone in an amount ratio of 0.3-0.5g:0.3-0.5g.
7. The method for preparing NaP molecular sieve / activated carbon composite material from coal gangue according to claim 1, characterized in that: In step S4, the preparation method of the oxidized molecular sieve includes the following steps: adding the carbon-coated molecular sieve and 98.0wt% sulfuric acid to a reactor at a temperature of 0-5°C and stirring, keeping warm and stirring for 10-15 minutes, adding sodium chlorate to the reactor, keeping the temperature of the reactor at 0-5°C and reacting for 2-4 hours, using a saturated sodium hydroxide solution to adjust the pH of the reaction system to 7, and post-treating to obtain the oxidized molecular sieve.
8. The method for preparing NaP molecular sieve / activated carbon composite material from coal gangue according to claim 7, characterized in that: The amount ratio of carbon-coated molecular sieve, 98.0wt% sulfuric acid and sodium chlorate is 5-8g:30-40g:3-5g, the stirring rate of the reactor is 80-120rpm, and the post-treatment includes: after the temperature of the reactor is raised to room temperature, the reaction liquid is filtered to collect the filter cake, the filter cake is washed with deionized water for 3-5 times, and the filter cake is placed in a drying oven at a temperature of 80°C and vacuum dried until the filter cake has a constant weight to obtain an oxidized molecular sieve.
9. The method for preparing NaP molecular sieve / activated carbon composite material from coal gangue according to claim 1, characterized in that: In step S4, the preparation method of the hydrophilic modifier comprises the following steps: A1, add trifluoroethyl methacrylate, 1-allyloxy-2,3-propylene oxide, 3-(methacryloyloxy)propyltrimethoxysilane, isocyanatoethyl methacrylate and toluene into a reaction kettle and introduce nitrogen protection, stir at room temperature for 10-15 minutes to obtain a reaction liquid precursor solution; A2. Add the reaction liquid precursor and azobisisobutyronitrile into the reactor and stir. Raise the temperature of the reactor to 70-80° C. and keep the temperature for 2-4 hours. Post-treat to obtain a hydrophilic modifier.
10. The method for preparing NaP molecular sieve / activated carbon composite material from coal gangue according to claim 9, characterized in that: In step A1, the amount ratio of trifluoroethyl methacrylate, 1-allyloxy-2,3-propylene oxide, 3-(methacryloyloxy)propyltrimethoxysilane, isocyanoethyl methacrylate and toluene is 5-8g:4-5g:10-12g:8-10g:80-100mL, and the stirring rate of the reactor is 80-120rpm; in step A2, the amount ratio of the reaction liquid precursor liquid and azobisisobutyronitrile is 50-60mL:2-3g.
Citation Information
Patent Citations
Coal gangue-based molecular sieve and alkali melting-hydrothermal preparation method thereof
CN114988426A
Cited By
Desulfurization purification method for preparing methanol purge gas from coke oven gas
CN119771157A
A desulfurization and purification method for methanol production from coke oven gas
CN119771157B